Strong adsorption of phosphate by amorphous lanthanum carbonate nano-adsorbents - Lu, Yifan (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
Phosphorus removal is a crucial aspect of controlling water pollution and eutrophication. In this study, the preparation of lanthanum carbonate (LC) nano-adsorbents for the efficient removal of phosphate (P) from water and wastewater was investigated. Results from XRD, SEM and Zeta potential analyses revealed that addition of magnesium ions and adjustment of the reaction temperature could control the morphology and microstructure of LC. Effects of initial pH, adsorbent dosage, contact time, and the water matrix on P adsorption were investigated. Batch adsorption experiments revealed that LC showed strong performance on P removal over a wide pH range (3.0 to 11.0). The kinetic data followed a pseudo-second-order model, and equilibrium data were well fitted by the Langmuir model with a maximum adsorption capacity of 112.9 mg P/g. Adsorption thermodynamics showed that the adsorption process was exothermic and spontaneous. Results of a monolayer model for single adsorption indicated that P could completely interact with two or more functional groups from the LC surface. In the presence of competing ions (F-, Cl-, SO42-, NO3-, and HCO3-), LC maintained high selectivity for phosphate. For a real effluent, the P concentration was efficiently reduced from 3.2 mg P/L to below 0.5 mg P/L at a dose of 0.5 g/L LC. All the results suggested that LC can serve as a promising adsorbent for P removal in a wide range of pH, and thus could meet the stricter discharge regulations from actual wastewater